2017
DOI: 10.1016/j.jpha.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of larotaxel and identification of its degradation products in alkaline condition

Abstract: Larotaxel, a new taxane compound prepared by partial synthesis from 10-deacetyl baccatin III, is active against tumors. In this research, a selective LC–MS method was developed and validated for the study of degradation kinetics of larotaxel, which was carried out in aqueous solutions with different pH (1.5, 3.0, 5.0, 6.5, 7.4, 9.0, 10 and 11.0) and temperature (0, 25, 37 and 45 °C). The linear range was 0.5–25 μg/mL, the intra- and inter-day precisions were less than 7.0%, and accuracy ranged from 97.4–104.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The minimum stability was found at pH 9.0 in all storage conditions. 26 In RT light condition, slightly similar stability was observed for pH 1.2, pH 5.0, pH 7.0 and pH 7.4 solvents.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The minimum stability was found at pH 9.0 in all storage conditions. 26 In RT light condition, slightly similar stability was observed for pH 1.2, pH 5.0, pH 7.0 and pH 7.4 solvents.…”
Section: Resultssupporting
confidence: 53%
“…The minimum stability was found at pH 9.0 in all storage conditions. 26 In RT light condition, slightly similar stability was observed for pH 1.2, pH 5.0, pH 7.0 and pH 7.4 solvents. In addition, regression coefficient (r 2 ) values and degradation rates of MH were calculated from the slope of the best-tted kinetic models.…”
Section: Degradation Kinetics Of Mhsupporting
confidence: 53%
See 1 more Smart Citation
“…The higher the activation energies, E a , the lesser the influence of temperature on the degradation reaction. Based on the result, temperature contributed to the drugs' degradation [22] and the pharmacokinetic profile of the animal model also contributed to its degradation.…”
Section: Determination Of Shelf-life Of the Drug Substancesmentioning
confidence: 99%
“…The calculated activation energies E a for the degradation of the drug samples were found to be high (E a > 50 kJ/mol.K), as shown in Table 1. The higher the E a is, the less the degradation reaction is influenced by temperature; the result indicated that temperature contributed to the degradation of the drugs [44] but sensitivity activities to the bacteria also contributed to the degradation.…”
Section: Shelf-life Determinationmentioning
confidence: 99%